2017
DOI: 10.1038/s41598-017-02347-2
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 mediates Lewis lung carcinoma-induced muscle wasting via coordinate activation of protein degradation pathways

Abstract: Cancer-induced cachexia, characterized by muscle wasting, is a lethal metabolic syndrome with undefined etiology. Current consensus is that multiple factors contribute to cancer-induced muscle wasting, and therefore therapy requires combinational strategies. Here, we show that Toll-like receptor 4 (TLR4) mediates cancer-induced muscle wasting by directly activating muscle catabolism as well as stimulating an innate immune response in mice bearing Lewis lung carcinoma (LLC), and targeting TLR4 alone effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
80
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 41 publications
11
80
1
Order By: Relevance
“…It would be also important to assess intramuscular Ucp1 expression in other models of atrophy. This will, however, likely require experiments with additional animal species because fatty infiltration is generally not observed during denervation atrophy [66][67][68][69] or cancer cachexia 65,[70][71][72] in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It would be also important to assess intramuscular Ucp1 expression in other models of atrophy. This will, however, likely require experiments with additional animal species because fatty infiltration is generally not observed during denervation atrophy [66][67][68][69] or cancer cachexia 65,[70][71][72] in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to the anti-inflammatory and protective effects of skeletal muscle mass as previously demonstrated 10 , we have shown that TLR4 activation is "directly" involved in metabolic disorders in AT such as triglyceride (TG) turnover and browning phenotype, both parameters relevant to the remodeling and dysfunction of AT induced by cachexia. Therefore, the results obtained with the ATOR treatment and TLR4 -/mice during the development of cachexia suggests that the TLR4 pathway plays a fundamental role in maintenance of AT during cachexia syndrome and is a strong candidate for novel anti-cachectic therapy development.…”
Section: Discussionmentioning
confidence: 74%
“…In a cancer cachexia animal model, genetic ablation of TLR4 elicited a less severe cachexia with an accompanying lower body weight loss, greater lean body and fat mass, and clinical evidence of reduced wasting compared with the age and weightmatched WT mice 11 . More recently, an elegant study showed that TLR4 is a crucial mediator of cancer-induced muscle wasting due to its integration of catabolic signaling by directly activating muscle protein degradation and indirectly increasing cytokine release 10 . Thus, TLR4 may be a critical therapeutic target for cancer cachexia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are packed in extracellular vesicles and delivered to skeletal muscle, where they bind to TLR4 to activate catabolic signaling pathways and production of inflammatory cytokines (8). A recent study has also shown that skeletal muscle wasting is partially rescued in whole-body TLR4-KO mice in response to growth of LLC tumors (9). However, how gene expression of other TLRs as well as MyD88 is regulated and their potential role and mechanisms of action in cancer-associated skeletal muscle wasting remained largely unknown.…”
Section: Discussionmentioning
confidence: 99%